Denosumab treatment in the management of patients with advanced prostate cancer: clinical evidence and experience. (March 2017) - Hegemann, Miriam; Bedke, Jens; Stenzl, Arnulf; Todenhöfer, Tilman
Osteoprotective therapies have become an essential component in the management of advanced prostate cancer (PC) patients as bone metastases (BMs) have a major impact on morbidity and mortality. Denosumab is a fully humanized antibody targeting the receptor activator of nuclear factor κB ligand (RANKL), which has been approved by the European Medicines Agency (EMA) in Europe and the United States (US) Food and Drug Administration (FDA) in the US for prevention of skeletal-related events (SREs) in patients with solid tumors and BMs, including PC. The clinical settings in which PC patients should be treated with denosumab are still discussed controversially. In a phase III study, denosumab significantly delayed SREs compared with zoledronic acid (ZA) in patients with metastatic castration-resistant PC (CRPC). In addition, denosumab showed superior effects on pain and health-related quality of life (QoL) in these patients. In patients with nonmetastatic CRPC, denosumab has been proven to significantly increase bone metastases-free survival. However, no significant benefits on cancer-specific and overall survival were observed and denosumab was not approved by the US FDA and EMA in this context. The effectiveness of denosumab in patients with castration-sensitive PC (CSPC) and BMs is also under discussion, as clinical trials with ZA in these patients have not shown significant benefits. Clinical data on the use of denosumab in CSPC are urgently needed.